2018
DOI: 10.12680/balneo.2018.217
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitro-oxidative stress on platelet aggregability in migraine patients in a Rehabilitation Hospital - a pilot study

Abstract: Introduction: Migraine is a common, chronic and disabling neurovascular disorder that is characterized by severe headache attacks. Pathogenesis of migraine is still unclear, different vascular, neurological, and neuroinflammatory mechanisms have been suggested. Nitric oxide (NO) plays a role during trigeminovascular inflammation associated with migraine attacks, and increased production can lead to increased platelet aggregability. Methods: 37 patients with migraine attack were compared with a control group (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Hemodynamic changes (characterized by hypo-perfusion), hypercoagulability status and altered endothelial functions are between pathophysiological mechanisms that are suggested to be associated with migraine [ 11 , 12 ]. Experimental and clinical studies showed that inflammation triggered and amplified by oxidative stress could constitute other mechanisms associated with migraine attacks [ 13 , 14 , 15 ]. Oxidative stress enhancement during migraine attacks can arise from different mechanisms, including a high rate of energy production by the mitochondria, calcium overload into the cells, neuronal excitotoxicity, neuroinflammation, the activation of microglia, or the activation of neuronal nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic changes (characterized by hypo-perfusion), hypercoagulability status and altered endothelial functions are between pathophysiological mechanisms that are suggested to be associated with migraine [ 11 , 12 ]. Experimental and clinical studies showed that inflammation triggered and amplified by oxidative stress could constitute other mechanisms associated with migraine attacks [ 13 , 14 , 15 ]. Oxidative stress enhancement during migraine attacks can arise from different mechanisms, including a high rate of energy production by the mitochondria, calcium overload into the cells, neuronal excitotoxicity, neuroinflammation, the activation of microglia, or the activation of neuronal nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between smoking and the patient's gender was also observed, as female smokers believed to have more severe attacks (31). On the one hand, smoking increases the production of nitric oxide and platelet aggregability (32), and nicotine causes intracranial vasoconstriction leading to the reflex release of vasodilator metabolites, therefore, triggers a migraine attack (33,34). On the other hand, light smoking increases the secretion of betaendorphins leading to a reduction in pain and anxiety (31,35).…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated oxidative stress parameters, peripapillary RNFL thickness, and macula thickness in migraine patients without aura who were not taking preventative medication. It also examined the link between oxidative stress and OCT findings [13,14]. This paper aims to study hypoperfusion during migraines and its Effect on the Retina.…”
Section: ____________________________________________________________...mentioning
confidence: 99%